2011
DOI: 10.1007/s11227-011-0578-4
|View full text |Cite
|
Sign up to set email alerts
|

A market-oriented hierarchical scheduling strategy in cloud workflow systems

Abstract: A market-oriented hierarchical scheduling strategy in cloud workflow systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(150 citation statements)
references
References 44 publications
0
148
0
Order By: Relevance
“…Liu et al [8] proposed an innovative instance-intensive cost-constraint workflow scheduling algorithm for Cloud which is called as Compromised-Time-Cost (CTC) considering the main factors cost and time that has user input and also incorporating the main characteristics of Cloud Computing. The results obtained from simulation showed that the proposed algorithm is able to achieve lower cost as compared to the other algorithms while maintaining the user designated deadline.…”
Section: Related Work Sadhasivam and Selvaranimentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [8] proposed an innovative instance-intensive cost-constraint workflow scheduling algorithm for Cloud which is called as Compromised-Time-Cost (CTC) considering the main factors cost and time that has user input and also incorporating the main characteristics of Cloud Computing. The results obtained from simulation showed that the proposed algorithm is able to achieve lower cost as compared to the other algorithms while maintaining the user designated deadline.…”
Section: Related Work Sadhasivam and Selvaranimentioning
confidence: 99%
“…Wu et al [8] had suggested a scheduling strategy which is market oriented that contains two level scheduling: service level and task level scheduling. Service level scheduling is responsible for assigning Task-to-Service viz.…”
Section: Related Work Sadhasivam and Selvaranimentioning
confidence: 99%
“…Before analysing the problem of scheduling, we should have a study of the execution conditions and time points of the dependent tasks firstly, and then schedule it according to the correspond scheduling strategy [5].…”
Section: The Analysis Of Tasks Executionmentioning
confidence: 99%
“…Laili, Tao [14] have combined the Service Composition Optimal Selection (SCOS) and Optimal Allocation of Computing Resources (OACR) into one-time decision in one console, named Dual Scheduling of Cloud Services and Computing Resources (DS-CSCR). Wu, Liu [16] have proposed a market-oriented hierarchical scheduling strategy in Cloud workflow systems.  2014…”
Section:  2013mentioning
confidence: 99%
“…Job scheduler is a vital part of any distributed system like Grid [11][12][13], Cloud [14][15][16][17] and P2P networks [18][19][20] which assigns jobs to suitable resources for execution. The scheduling of a task workflow in a distributed computing platform is a well-known NP-hard problem [21].…”
Section: Introductionmentioning
confidence: 99%